THE MECHANISM FOR ENSURING ENTERPRISE ECONOMIC SECURITY BASED ON MARKETING INNOVATIONS - ZAKUSILO, Vadym; HAVLOVSKA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates the theoretical foundations and presents a scientific model of the mechanism for ensuring the economic security of enterprises based on marketing innovations. It is demonstrated that under conditions of digital transformation, marketing innovations evolve into a system-forming factor that integrates informational, strategic and behavioural components of management, thereby strengthening the resilience of enterprises operating in an environment of uncertainty and intensified risks. The proposed model identifies key structural elements of the mechanism, including actors, objects, principles, resources and tools, as well as the logic of their interaction across technological-digital, strategic-managerial and customer-behavioural components. Particular attention is paid to the role of digital technologies, analytical platforms, CRM systems and personalised service models in enhancing the capacity of enterprises to detect threats, respond to market fluctuations and maintain stable stakeholder relations. The research findings show that marketing innovations contribute to the formation of a new managerial paradigm of economic security, focused on reducing behavioural, informational, reputational and market risks, improving adaptive capabilities and reinforcing long-term competitiveness. The practical significance of the results lies in the possibility of applying the mechanism to improve the stability of business models, optimise decision-making processes and support sustainable development in dynamically changing market conditions. Prospects for further research include the development of methodological tools for assessing the impact of marketing innovations on economic security and the creation of sector-specific modifications of the proposed mechanism.